Air Pollution and Health - A Science-Policy Initiative - Academy of Science of South Africa; Brazilian Academy of Sciences; German National Academy of Sciences Leopoldina; U. S. National Academy of Medicine; U. S. National Academy of Sciences (Ubiquity Press, 2019)
Air pollution is a major, preventable and manageable threat to people's health, well-being and the fulfillment of sustainable development. Air pollution is estimated to contribute to at least 5 million premature deaths each year across the world. No one remains unaffected by dirty air, but the adverse impacts of air pollution fall most heavily upon vulnerable populations, such as children, women, and people living in poverty - groups to whom States have special obligations under international human rights law. The National Academies of Sciences and Medicine of South Africa, Brazil, Germany and the United States of America are calling upon government leaders, business and citizens to take urgent action on reducing air pollution throughout the world - to the benefit of human health and well-being, to the benefit of the environment and as a condition towards sustainable development. Air pollution is a cross-cutting aspect of many UN Sustainable Development Goals.